Ocena skuteczności instrumentów polityki antymonopolowej na przykładzie rynku transportu kolejowego - Zielenkiewicz, Małgorzata (The Efficiency of Antimonopolistic Policy Instruments in the Context of Railroad Transport, 2009)
The paper analyzes instruments used in antimonopolistic policy for solving a problem of non sufficient competition in railroad transport. Rail is an example of the market with a strong tendency towards concentration. Neither free market policy nor nationalization of railroad transport did solve this problem. The aim of the paper is to present different public instruments used in transport policy and to identify which types of public regulations are able to bring effective solutions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 921-929